Extracts from Argentinian native plants exhibit antifungal activity against multidrug-resistant Candida species = Extractos de plantas nativas argentinas exhiben actividad antifúngica contra especies de Candida multirresistentes - Etchecopaz, Alenadro A. (2025)
Infections caused by the genus Candida have acquired considerable significance in recent years due to the enhanced susceptibility of immunocompromised hosts. There have been increasing reports of multidrug resistance (MDR) in several Candida species, posing a major hurdle to antifungal therapy. Accordingly, exploring and developing novel anti-Candida agents has become a priority. In this study, we assessed the antifungal activity of seven methanolic extracts from the Argentinian native plants Peltophorum dubium, Schinus areira, Parastrephia quadrangularis and Lantana balansae against clinical isolates of different wild-type and MDR isolates of Candida. Synergism with fluconazole was also evaluated. All plant extracts showed antifungal activities against different Candida species, including MDR isolates such as C. haemulonii. Highly active extracts from these native plants provide promising sources of compounds for potentiating the antifungal effect of fluconazole. Further investigation of the chemical constituents of the extracts and their cytotoxicity is needed to develop plant-derived anti-Candida agents.